Green marketing practices in Malaysian manufacturing industries - Omar, Roaimah; Samuel, Rachel (2012)
In many Asian countries, firms are required by the government to consider sustainable development as an integral aspect of the firms' business strategy. Besides, the growing demand for environmentally friendly products amongst consumers have driven many businesses to be concerned about green marketing and sustainable development. Implementation of environmental standards amongst companies is costly and difficult. In Malaysia, manufacturing firms play an important in continuous economic growth and export contribution. Manufacturing industries contribute significantly to GOP and national development. This study is undertaken to examine the stages of environmental management of manufacturing firms and the extent of embracing green marketing strategies. This study also expects to examine the green initiatives undertaken by the firms. The net outcome is to assess the impact of environmental engagement, environmental orientation and environmental marketing management.